Risks and Benefits of Technologies for Organizational Change Enablement - A Role Theory Perspective - Brechtelsbauer, Bastian; Laumer, Sven (Proceedings of the 57th Hawaii International Conference on System Sciences, 2024)
As organizational change is omnipresent yet often challenging, organizations increasingly employ information technology (IT) to support and improve their change management. We refer to these technologies as change management mediation technologies (CMMTs). Despite their increasing relevance in practice, little is known about their successful implementation and usage as well as potential risks and benefits they encompass. To this end, we present findings from a multi-case study on two companies that utilize a CMMT to enable their employees for ongoing and future change projects, focusing especially on the digital transformation. We use role theory to describe and explain how CMMT usage can change employees’ roles and how this is connected to different risks and benefits for individuals and organizations. Thereby, we add to the growing literature on CMMTs and showcase a novel application of role theory in IS. Moreover, practical implications and opportunities for further research are discussed.<br
Keywords: Organizational Change; Information Technology; Digital Transformation; Role Theory; Case Study